Modelling of High-Velocity Impact on Woven Carbon Fibre-Reinforced Plastic Laminate - Nenad Djordjevic; Rade Vignjevic; Kevin Hughes; Tom De Vuyst (Applied Sciences)
This paper describes a constitutive model for progressive damage in carbon fibre-reinforced composites (CFRPs), developed in the framework of thermodynamics and coupled with a vector equation of state. This made the constitutive model capable of modelling shock wave propagation within orthotropic materials. Damage is incorporated in the model by using reduction in the principal material stiffness based on the effective stress concept and the hypothesis of strain energy equivalence. Damage evolution was defined in terms of a modified Tuler–Bucher criteria. The constitutive model was implemented into Lawrence Livermore National Laboratory (LLNL) DYNA3D nonlinear hydrocode. Simulation results were validated against post-impact experimental data of spherical projectile impact on an aerospace-grade woven CFRP composite panel. Two plate thicknesses were considered and a range of impact velocities above the ballistic limit of the plates, ranging from 194 m/s to 1219 m/s. Other than for the size of the delamination zone in the minor material direction, the discrepancy between the experiments and numerical results for damage and delamination in the CFRP target plates was within 8%.